Green Sukuk and the Political Economy of Sustainability: Rethinking Islamic Finance beyond Market Logics - Abdulrhman Mohmmad Alamoudi (Transpublika Publisher, 2026)
This study critically examines whether green sukuk represent a genuine transformation in Islamic finance or primarily reproduce the market-oriented logics of contemporary sustainable finance. It develops an integrated analytical framework combining political economy, financialization, assetization, and Maqasid al-Shariah to evaluate green sukuk beyond their legal structure and financial performance. Employing a qualitative conceptual methodology, the study draws on a critical literature review, documentary analysis of international sustainability and Islamic finance standards, and theory-driven interpretive analysis. The findings indicate that while green sukuk have expanded the participation of Islamic finance in climate-related investment and sustainable development, their institutional evolution remains largely embedded within global market-based sustainability governance. Consequently, environmental legitimacy is often assessed through financial and regulatory frameworks rather than broader ethical objectives. From a Maqasid al-Shariah perspective, the study argues that the distinctiveness of Islamic sustainable finance should be evaluated according to its contribution to justice, public welfare, environmental stewardship, and intergenerational responsibility, rather than contractual compliance alone. The paper contributes to the literature by proposing a Maqasid-oriented paradigm for evaluating green sukuk beyond market-oriented performance criteria. This perspective provides a broader conceptual foundation for future research, policy development, and governance reforms aimed at strengthening the ethical contribution of Islamic finance to sustainable development.